Detection of Brucella canis-induced reproductive diseases in a kennel - Gyuranecz, Miklós; Szeredi, Levente; Rónai, Zsuzsanna; Dénes, Béla; Dencso, László; Dán, Ádám; Pálmai, Nimród; Hauser, Zsófia; Lami, Erzsébet; Makrai, László; Erdélyi, Károly; Jánosi, Szilárd (Journal of veterinary diagnostic investigation, 2011)
Brucella spp. were isolated from an abortion case submitted for laboratory examination 8 months after the first clinical symptoms appeared in a kennel consisting of 31 dogs. Pathological investigations revealed the parallel presence of necrotic placentitis and the strong immunostaining of trophoblast cells by immunohistochemistry (IHC) using hyperimmune rabbit anti-Brucella canis primary antibodies. The rapid slide agglutination test was positive in 7 of 31 (23%) cases. The organism B. canis was successfully cultured from the blood, tissues, or vaginal swabs of only 3 of 31 (10%) cases. The isolated strains were identified as B. canis based on their colony morphology and agglutination with R sera. The strains were initially misidentified as B. suis with the "Bruce-ladder" method, and were subsequently correctly identified as B. canis with a single nucleotide polymorphism (SNP) typing test. Three culture-positive cases and 3 culture-negative cases with histories of reproductive disorders were selected and examined for the presence of B. canis infection using histopathology, IHC, and polymerase chain reaction (PCR) assays. Characteristic histologic lesions were found in all of the 6 animals, whereas IHC and PCR yielded positive results only in single cases from both groups. The results imply that all cases of canine abortion should be examined for brucellosis by bacterial culture of aborted fetuses and placentas. Immunohistochemical examination of placentas is also recommended because it is a quick and sensitive technique compared with bacterial culture. Multiple methods (i.e., serology, blood, and genital bacterial cultures) should be applied simultaneously and repeatedly for the reliable screening of B. canis infection in live individuals.